Український національний рух на Буковині другої половини ХІХ – початку ХХ ст. у взаєминах з національними рухами інших народів краю: конкуренція та співпраця - Dobrzhanskyi, Oleksandr (AKADEMIA POMORSKA W SŁUPSKU, 2022)
The article analyzes the relationship between the Ukrainian, Romanian, German, Jewish, Polish national movements in Bukovyna in the late 19th – early 20th century. It has been proven that despite fierce political competition, tolerant, parliamentary methods of struggle prevailed in interethnic relations. There was constructive cooperation in solving the pressing issues of Bukovyna.
Keywords: Bukovyna; Ukrainian; Romanian; German; Jewish